Biallelic NSUN3 variants cause diverse phenotypic spectrum disease: from isolated optic atrophy to severe early-onset mitochondrial disorder - Jurkute, Neringa; Brennenstuhl, Heiko; Kustermann, Monika; Van Haute, Lindsey; Mutti, Christian D.; Bugiardini, Enrico; Handa, Takayuki; Shimura, Masaru; Petzold, Axel; Acheson, James; Robson, Anthony G.; Macken, William L.; et al. (Investigative ophthalmology & visual science, 2025)
Primary mitochondrial disorders (PMDs) are a clinically heterogeneous group of genetic disorders that can affect many tissues, with a broad phenotypic spectrum ranging from isolated organ involvement to severe early-onset multisystem disease. Visual loss from optic atrophy is a frequent clinical manifestation of mitochondrial cytopathies. This study aimed to identify the missing heritability in previously unsolved cases of suspected isolated or syndromic optic neuropathy. Based on three recent reports on biallelic NSUN3 variants causing early-onset PMD, we explored in detail the genetic and clinical spectrum of NSUN3-associated disease. Affected individuals were analyzed by exome or genome sequencing. In silico variant analysis and functional assays were performed to investigate the consequences of the identified variants. Detailed phenotyping data were collected from medical records and direct questioning after the identification of candidate-likely pathogenic variants. Interrogation of exome and genome sequencing data led to the identification of six candidate NSUN3 variants in eight affected individuals from five unrelated families (including a previously reported case). A broad phenotypic spectrum was observed ranging from isolated optic atrophy to severe early-onset PMD. Identified NSUN3 variants impairing NSUN3 activity are located within the S-adenosylmethionine-dependent methyltransferases domain and loss of function variants were associated with a more severe phenotype. Remarkably, bilateral optic atrophy was a unifying clinical feature observed in almost all affected individuals. Pathogenic or likely pathogenic biallelic variants in NSUN3 disrupt mt-tRNAMet methylation and mitochondrial translation leading to mitochondrial disease ranging from mild isolated optic atrophy to a severe multisystemic phenotype with possible limited life expectancy.